A comparative study of intracervical Foley’s catheter and intracervical PGE2 gel for pre-induction cervical ripening - Murmu, Sunita; Dwivedi, Chetna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Induction of labor is a common procedure in obstetrics. It is usually performed when risk of continuing a pregnancy is more than benefit of delivery. Cervical ripening has got a close relationship with the success rate of delivery. Although there are many methods for cervical ripening, in this study Foley’s catheter and intra-cervical PGE2 gel are compared for labor induction and cervical ripening. Methods: This is a prospective randomized comparative study, undertaken in the department of obstetrics and gynecology, Tata Main Hospital, Jamshedpur. 70 cases in which labor was induced with Foley’s catheter were compared to other 70 cases who were induced with PGE2 gel. Results: The commonest indication for induction in Foley’s and PGE2 gel group was pregnancy induced hypertension. There was significant increase in the post induction Bishop’s score in both the groups. The induction to delivery interval was significantly lower in Foley’s group as compared to PGE2 group (p<0.0001). Neonatal outcomes were comparable in both groups. Incidence of side effects were more in PGE2 group. Conclusions: Foley’s catheter is safe and effective method for induction of labor compared to PGE2 gel with significant improvement in Bishop’s score and shorter induction delivery interval.